Pengaruh Advertising Value dan Brand Awareness Terhadap Purchase Intention Pada Produk OPPO Reno8 T Series - M. Syah Syeh Iskhaq; Sri Setyo Iriani (Jurnal Ilmiah Wahana Pendidikan, 2023)
Purchase intention is consumer behavior that arises in response to objects that indicate the desire of consumers to make purchases. Some factors that can affect purchase intention are advertising value and brand awareness. This study aims to discuss the influence of advertising value and brand awareness on purchase intention on OPPO Reno8 T Series products. This research is a quantitative research. The sampling technique used was the judgmental sampling technique with a total of 210 respondents. The distribution of questionnaires was carried out online by measuring answers using a four-level Likert scale. The statistical analysis used is multiple linear regression using the SPSS application. The results showed that advertising value and brand awareness affect purchase intention. The implications based on this study show that the OPPO brand is expected to increase consumer brand awareness such as creating interesting marketing content, being active in social media, and holding events so that brand awareness can further influence purchase intention.